Excessive EDTA induces morphologic changes in bone marrow smears that mimic specific features of dysplasia. Issue 2 (13th October 2012) - Lee, S.‐H.; van der, C.; Mayson, E.; Desai, S.
Summary Introduction The WHO 2008 guidelines recommend that bone marrow (BM) slides for the morphological assessment of dysplasia should be made from freshly obtained BM specimens, and that specimens exposed to anticoagulants for more than two hours are unsatisfactory. However, BM aspirates may be exposed to excessive concentrations of anticoagulant, due to underfilling of the tube or inadequate mixing of the specimen. Here, we document the morphologic changes in BM smears resulting from exposure to excessive concentrations of ethylenediaminetetraacetic acid (EDTA). Methods Subjects with normal morphology in BM smears without anticoagulant were studied. Smears without anticoagulant and smears made from BM stored in excessive EDTA for 2 h at room temperature were stained with May–Grünwald Giemsa, and cell morphology was evaluated microscopically. Neutrophil and megakaryocyte size were measured using a calibrated microscope eyepiece graticule. Results Excessive EDTA concentrations induced progressive nuclear and cytoplasmic contraction with respective membrane damage, cell smudging and pyknotic nuclei. In the granulocytic and megakaryocytic series, hypolobated neutrophils, small neutrophils and micromegakaryocytes were increased in number. In erythroblasts, nuclear contour irregularities were induced, but in general, artifactual changes did not mimic dyserythropoiesis. With excessive EDTA concentrations, morphologic features of erythroblasts and megakaryocytes were obscured by nuclear and cytoplasmic contraction. Conclusion Excessive EDTA induces morphologic changes in BM smears that mimic the specific dysplastic features of hypolobated neutrophils, small neutrophils, and micromegakaryocytes. BM aspirates should be collected into an appropriate concentration of EDTA to minimize such artifacts.